2013
DOI: 10.1080/19443994.2013.846460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and metal uptake capacity of a new polyaniline and poly(acrylic acid) grafted sodium alginate/gelatin adsorbent

Abstract: A B S T R A C TThe present work reports the development of new (sodium alginate-gelatin (SAG))-g-poly (acrylic acid)/polyaniline (SAPAPN) from sodium alginate/gelatin blend by cross-linking with glutaraldehyde, followed by grafting with poly(acrylic acid) and polyaniline by free radical polymerization using ammonium persulfate. The structure, thermal stability, and morphology of SAPAPN adsorbent was characterized by Fourier transform infrared spectroscopy, thermo gravimetric analysis, and scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The Q e values are reported to be 43.51 (Cu(II)) and 240.64 (Ni(II)). Moreover, the development of membranes from polyaniline and poly(acrylic acid)-g-sodium alginate/gelatin was also reported [ 31 ]. The Q e values of this study were reported as 53.29 for Cu(II) and 129.28 for Ni(II).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Q e values are reported to be 43.51 (Cu(II)) and 240.64 (Ni(II)). Moreover, the development of membranes from polyaniline and poly(acrylic acid)-g-sodium alginate/gelatin was also reported [ 31 ]. The Q e values of this study were reported as 53.29 for Cu(II) and 129.28 for Ni(II).…”
Section: Resultsmentioning
confidence: 99%
“…reported to be 43.51 (Cu(II)) and 240.64 (Ni(II)). Moreover, the development of membranes from polyaniline and poly(acrylic acid)-g-sodium alginate/gelatin was also reported [31].…”
Section: Ion Exchange Capacity Oxidative Stability Proton Conductivity and Methanol Permeability Studiesmentioning
confidence: 98%
See 3 more Smart Citations